Implementation of Tsukamoto Fuzzy Logic for Watering Interval Control in Mini Greenhouse Temperature and Humidity Monitoring System with Aeroponic Method - Pramana, Revata Dendi Aurix; Baswara, Ahmad Raditya Cahya (Universitas Ahmad Dahlan, 2024)
Agriculture in Indonesia faces challenges in the use of modern technology, resulting in a lack of optimisation in land management and crop yields. Greenhouses, also known as 'hothouses', have been developed using environmental sensor technology and microcontrollers to increase the efficiency of crop management. The use of Tsukamoto fuzzy logic is one of the solutions to improve this system. However, the increasingly popular microgreens have the disadvantage of losing nutrients when stored for long periods. Nevertheless, microgreens remain an attractive alternative for urban agriculture with limited land because of their fast growth and high nutrient content, offering more value than buying them from the store. The mini-greenhouse's temperature and humidity monitoring system uses the aeroponic cultivation method and adopts Tsukamoto fuzzy logic control with nine fuzzy rules to manage the watering interval. The temperature and humidity measurement results are sent online to the Internet for real-time monitoring. This research successfully designed an aeroponic system for growing caisim mustard greens, conducted IoT monitoring using ThingSpeak, and implemented watering control using Tsukamoto fuzzy logic. The results showed that the plants reached a height of 25 cm with 9 leaves and a leaf width of 8 cm. The watering interval method effectively reduced the power consumption to 3.6 times lower than 24-hour continuous watering, showing a significant contribution to energy management in aeroponic systems.